Some Comparisons between Hesiod’s Theogony and Francisco de Goya’s Saturn Devouring His Son - Berndt, Jorge Antonio; Bernartt Silva, Marianna; de Melo Oliveira, Valdeci Batista (Lingüística y Literatura, 2021)
After Hesiod’s epopee, depictions of the swallowing scene of Chrono’s children became frequent in the western iconography, with reinterpretations made since the classic antiquity until the romantic period. Thus, by means of a comparative and semiotic perspective, it is sought to analyze the translation of the Theogony’s second cosmic phase produced by Francisco de Goya, in Saturn Devouring His Son. It is concluded that the poem’s composition is stablished in the absolute/epic past, while the painting’s one in the uncanny. Besides, it is identified, in the texts’ relation, the transversality of the semiosis process in verbal and nonverbal expressions